Pilot Application of a Savonius Wind Turbine-Based Residential Street-Lighting System in Madyopuro, Malang - Novan Habiburrahman; Ari Sam Primadiarta; Djarot Winoto; Slamet Slamet (⁠International Journal of Asia Pacific Community Service, 2026)
Insufficient lighting at selected residential access points and limited public familiarity with small-scale renewable energy are common challenges in densely built neighborhoods. This community service program developed a pilot Savonius vertical-axis wind turbine as a supplementary power source for an LED residential street-lighting system at Perumahan Bulan Terang Utama, RT 04/RW 18, Madyopuro, Kedungkandang, Malang, East Java. The independently funded activity did not involve a formal institutional partner. The work included site assessment, energy sizing, rotor and support-structure fabrication, generator and battery integration, installation, commissioning, safety communication, and preparation of a maintenance framework. The prototype used a two-stage Savonius rotor with a 1.44 m² swept area, a permanent-magnet generator, rectifier and buck-boost converter, charge controller, 12 V battery, dusk-to-dawn control, and a 6 W LED lamp. Engineering calculations using a rotor power coefficient of 0.15 and realistic conversion efficiencies indicated electrical outputs of approximately 1.6–12.2 W at wind speeds of 3–6 m/s. Under a representative low-wind daily scenario, the projected energy production was approximately 52 Wh/day, sufficient for about 7.5 hours of LED operation after storage losses. The prototype provides a practical platform for demonstrating energy conversion and maintenance requirements. Long-term wind measurement, structural verification, electrical-safety review, and battery monitoring are required before broader replication.